The Feasibility of Using the BrightHearts Biofeedback‐Assisted Relaxation Application for the Management of Pediatric Procedural Pain: A Pilot Study. - Burton, Karen L.O.; Morrow, Angela M.; Beswick, Brooke V.; Khut, George P. (Pain Practice, 2018)
Objective: The objective of this pilot study was to assess the acceptability and feasibility of using BrightHearts, a biofeedback‐assisted relaxation application (app), in children undergoing painful procedures. Methods: Thirty children 7 to 18 years of age undergoing a medical procedure (peripheral blood collection, botulinum toxin injection, or intravenous cannula insertion) participated. Participants used BrightHearts, a heart rate–controlled biofeedback‐assisted relaxation training app delivered via an iPad with heart rate measured through a pulse oximeter worn on the ear or thumb. Feasibility was assessed through observations and patient, parent/carer, and healthcare professional feedback. Patient, parent/carer, and healthcare professional satisfaction with BrightHearts was rated using investigator‐developed surveys. Results: Eighty‐three percent of child participants reported that they found BrightHearts helpful during the procedure and that they would use BrightHearts again. All parents and 96% of healthcare professionals indicated they would use BrightHearts again. Sixty‐four percent of healthcare providers perceived that BrightHearts assisted with the ease of performing the procedure. Qualitative analyses found 2 themes: (1) BrightHearts calms through providing distraction and biofeedback and (2) the impact of BrightHearts on the procedure. Conclusions: This pilot study demonstrates the feasibility of using biofeedback‐assisted relaxation delivered via the BrightHearts app in children undergoing peripheral blood collection and cannulation. Future studies are required to evaluate BrightHearts' efficacy in reducing pain and anxiety during painful procedures and distinguish the effects of a biofeedback‐mediated app from distraction.